The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acssuschemeng.5b01336
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Carbon Dioxide to Formate on Tin–Lead Alloys

Abstract: Electrochemical reduction of carbon dioxide (CO2) to formate (HCOO–) in aqueous solution is studied using tin–lead (Sn–Pb) alloys as new electrocatalysts. In electrochemical impedance spectroscopy (EIS) measurements, lower charge-transfer resistance is observed for the alloy electrodes when compared to the single metal electrodes such as Sn and Pb. The results of X-ray photoelectron spectroscopy (XPS) and cyclic voltammetric (CV) analysis show that the Sn in the Sn–Pb alloys facilitates the formation of oxidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(111 citation statements)
references
References 48 publications
2
108
1
Order By: Relevance
“…Among the post transition metals (Hg, Cd, Pb, Tl, In, Sn, and Bi) with high hydrogen overpotential and negligible CO adsorption to reduce selectively CO 2 to formate in aqueous medium, lead appears to be the most straightforward and suitable cathode material for technical applications, since it combines the high‐overpotential for the parasitic hydrogen evolution reaction (HER) with lower toxicity than cadmium and mercury ,. Bimetallic metal alloys have also been applied to CO 2 RR aiming at boosting formate production due to synergistic interactions between two transition metals, or a transition metal and copper . Recently, we investigated leaded bronze as a novel cathode material for a variety of electro‐organic reactions that features the catalytic performance of lead but exhibits a higher mechanical and chemical stability .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Among the post transition metals (Hg, Cd, Pb, Tl, In, Sn, and Bi) with high hydrogen overpotential and negligible CO adsorption to reduce selectively CO 2 to formate in aqueous medium, lead appears to be the most straightforward and suitable cathode material for technical applications, since it combines the high‐overpotential for the parasitic hydrogen evolution reaction (HER) with lower toxicity than cadmium and mercury ,. Bimetallic metal alloys have also been applied to CO 2 RR aiming at boosting formate production due to synergistic interactions between two transition metals, or a transition metal and copper . Recently, we investigated leaded bronze as a novel cathode material for a variety of electro‐organic reactions that features the catalytic performance of lead but exhibits a higher mechanical and chemical stability .…”
Section: Figurementioning
confidence: 99%
“…We rationalize the product selectivity of mechanically polished CuSn 7 Pb 15 electrocatalyst for CO 2 RR as follows: considering that the active surface is constituted by two well distinct phases (a Pb‐rich almost Cu‐free Pb/Sn phase and a Cu‐rich Cu/Sn phase) and that the typical products formed on them do not decompose on each other, we expect a cathode product selectivity composed of a mixture of their typical product distributions. The main chemical produced by either pristine Pb or PbSn alloys upon CO 2 RR in aqueous medium is HCOO − usually exceeding the amount of evolved H 2 from the parasitic HER in a wide potential range ,,,,,. On the other hand, the catalytic properties of the Cu‐rich Cu/Sn phase could be dominated either by its major component, by the overall alloy ensemble or by a combination of both.…”
Section: Figurementioning
confidence: 99%
“…The competitive interaction of H + /water with two metal centers may tune the binding strength of intermediates and control the reaction pathway to accelerate the reaction rate of CO 2 reduction on the surface. A few recipes of alloying have been developed for the synthesis of Cu‐based or Sn‐based electrocatalysts for CO 2 RR, including CuPd, CuPt, CuAu, CuAg, CuIn, CuZn, CuSn, SnAg, SnPd, SnPb, etc. For CuSn bimetallic systems as a kind of potential catalysts, previous research works have shown that the control of their composition provided a promising approach for improving the electrocatalytic properties for CO 2 reduction .…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al . fabricated Sn−Pb alloy catalyst deposited on a carbon paper . The alloy catalyst showed the higher selectivity and current density for the HCOO − production compared to Sn and Pb electrodes.…”
Section: Research Trends In Electrochemical Reduction Of Co2 At the Ementioning
confidence: 99%